Influence of partial replacement of cement by biomass ashes on cement-wood composites properties - Silva, Maria Fernanda Felippe [UNESP]; Silva, João Vítor Felippe; Franco, Mariana Pires [UNESP]; Lopes, Nathaly Proença [UNESP]; Sousa, Jeniffer Cristiane Rodrigues [UNESP]; de Campos, Cristiane Inácio [UNESP] (Universidad Nacional de Colombia, 2024)
The aim of this work was to evaluate the physical and mechanical properties of cement-wood composites with the addition of biomass ashes at different levels (0, 5, 10, 15, 20, and 25%). The composites were produced using Portland cement CPII, Eucalyptus grandis particles, and ashes from eucalyptus wood. The tests followed the NBR 7215 (2019) and ASTM E1876 (2022) standards, density, 24-hour thickness swelling, 24-hour water absorption, dynamic modulus of elasticity from non-destructive testing, static modulus of elasticity, and compressive strength at 28 days tests were carried out. After the tests, statistical analysis was performed to verify if there were statistically differences between the means at a 5% level of significance. The partial replacement of cement with ashes shows potential, especially with a 5% replacement, due to better physical and mechanical properties.
Influencia de la sustitución parcial de cemento por cenizas de biomasa en las propiedades de compuestos de cemento y madera
Keywords: cementitious composite; mechanical properties; physical properties; residues use